2011
DOI: 10.1038/ejcn.2011.87
|View full text |Cite
|
Sign up to set email alerts
|

Potential and requirements for a standardized pan-European food consumption survey using the EPIC-Soft software

Abstract: Given the suitability of EPIC-Soft as standardized dietary assessment tool in European dietary monitoring, the proposed strategy toward a pan-European food consumption survey is to prepare well, to allow flexibility in national extensions and to start with a limited number of countries that are interested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 30 publications
1
32
0
Order By: Relevance
“…Some other strengths and the potential of this standardized computerized 24-HDR method reported by users within or outside the EFCOVAL network include its application to a wide range of different populations, the relatively high participation rate and the potential for a telephone approach as a validated alternative (Brustad et al, 2003;Ocké et al, 2011). In case of a telephone approach, the picture book is provided in advance (either handed over personally or send by post) with a note not to open it before being contacted by an interviewer.…”
Section: S7mentioning
confidence: 99%
See 1 more Smart Citation
“…Some other strengths and the potential of this standardized computerized 24-HDR method reported by users within or outside the EFCOVAL network include its application to a wide range of different populations, the relatively high participation rate and the potential for a telephone approach as a validated alternative (Brustad et al, 2003;Ocké et al, 2011). In case of a telephone approach, the picture book is provided in advance (either handed over personally or send by post) with a note not to open it before being contacted by an interviewer.…”
Section: S7mentioning
confidence: 99%
“…The advantages, limitations and requirements to use EPIC-Soft in the context of pan-European dietary monitoring and the results on the validity of EPIC-Soft for specific purposes of future pan-European monitoring surveys are reported elsewhere (Crispim et al, 2010(Crispim et al, , 2011Ocké et al, 2011;Huybrechts et al, 2011a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Within the EFCOVAL project it was estimated that this would take 2 person months for 200 interviews (Ocke et al, 2011) Median energy intake (kJ) and median estimated PAL (a) level by country, study protocol, sex and age class and the ratio"s of median energy intake and of median estimated PAL level for the two study protocols The present document has been produced and adopted by the bodies identified above as author(s). Given these crude estimates, the PAL values are not suitable to estimate the prevalence of low and high energy reporters in these pilot studies.…”
Section: Quantification Of Foods and Recipesmentioning
confidence: 99%
“…In the EFCOSUM and EFCOVAL projects, EPIC-Soft was mentioned as the preferred software for 24-h diet recalls in adults (Brussaard et al, 2002;Ocke et al, 2011;Slimani et al, 2011). The EPIC-Soft program is a standardised 24-h recall program that was initially developed by IARC in the 1990"s in the frame of the EPIC study (Slimani et al, 1999;Slimani et al, 2000).…”
Section: Study Strengths and Limitations With Recommendation To Efsamentioning
confidence: 99%
“…Calculations for young children were performed using food consumption data of the Dutch National Food Consumption Survey (DNFCS)-Young children (Ocké et al, 2008). This survey covers the dietary habits of young children aged 2 to 6 years and was conducted in 2005 and 2006.…”
Section: Intake Calculationsmentioning
confidence: 99%